2017
DOI: 10.1158/1078-0432.ccr-16-0387
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor in Ovarian Cancer Inhibits Tumor Immunity through the Accumulation of Myeloid-Derived Suppressor Cells

Abstract: VEGF expression in ovarian cancer induced MDSCs, inhibited local immunity, and contributed to poor prognosis. Clin Cancer Res; 23(2); 587-99. ©2016 AACR.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
193
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 232 publications
(201 citation statements)
references
References 51 publications
4
193
2
2
Order By: Relevance
“…26 Although the precise molecular mechanism for the differentiation of MDSCs is yet to be defined, the expansion and accumulation of these cells are known to be mediated by granulocyte-macrophage colony-stimulating factor (GM-CSF), vascular endothelial cell growth (VEGF) and IL-4. 27,28 In this study, we showed that the frequency of which is in line with a prior report. 10 It is known that HCV infection can lead to inflammation in the liver and the secretion of inflammatory cytokines, which may result in damage to hepatocytes and the release of ALT in the blood.…”
Section: Mdscs From Chc Patients Suppress Autologous T-cell Proliferasupporting
confidence: 93%
See 1 more Smart Citation
“…26 Although the precise molecular mechanism for the differentiation of MDSCs is yet to be defined, the expansion and accumulation of these cells are known to be mediated by granulocyte-macrophage colony-stimulating factor (GM-CSF), vascular endothelial cell growth (VEGF) and IL-4. 27,28 In this study, we showed that the frequency of which is in line with a prior report. 10 It is known that HCV infection can lead to inflammation in the liver and the secretion of inflammatory cytokines, which may result in damage to hepatocytes and the release of ALT in the blood.…”
Section: Mdscs From Chc Patients Suppress Autologous T-cell Proliferasupporting
confidence: 93%
“…For human MDSCs, the M‐MDSCs subset mainly express CD14, whereas the G‐MDSCs do not express CD14 . Although the precise molecular mechanism for the differentiation of MDSCs is yet to be defined, the expansion and accumulation of these cells are known to be mediated by granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), vascular endothelial cell growth (VEGF) and IL‐4 . In this study, we showed that the frequency of G‐MDSCs was positively correlated with the concentration of serum HCVc in patients with CHC, suggesting that circulating HCVc plays a role in the development of G‐MDSCs and may mediate immune suppression.…”
Section: Discussionmentioning
confidence: 81%
“…Horikawa et al have shown recently that the VEGF-A/VEGFR2 pathway increases intratumoral MDSCs and promotes tumor progression in a mouse ovarian cancer model. They also showed that VEGF expression correlated with MDSCs infiltration in human samples from the peritoneum of ovarian cancer patients with disseminated disease (67). Besides these effects on immunoregulatory cells, a direct inhibition of conventional T cells by VEGF-A has been reported (68).…”
Section: Hypoxia In Rt-treated Tumors and Immune Regulation By Hif-1αmentioning
confidence: 97%
“…The VEGF-driven accumulation of CD33 + myeloid-derived suppressor cells (MDSCs), particularly in the omentum, also correlates with a failure to accumulate CD8 + TILs, the suppression of T cell function and a poor prognosis in ovarian cancer patients [91]. Similarly, CD33 + MDSCs that accumulate in peritoneal ascites fluid of ovarian cancer patients express nitric oxide synthase-2 (NOS2) and produce NO [92], which promotes the differentiation of Th17 cells and impairs the function of Th1 and CD8 + T cells.…”
Section: Peritoneal Tumor Metastasis In the Omentummentioning
confidence: 99%